A Second Family with Myhre Syndrome Caused by the Same Recurrent SMAD4 Pathogenic Variation (p.Arg496Cys) - ALAVANDA, CEREN (My University, 2023)
Introduction: Myhre syndrome (MS; OMIM #139210) is a rare connective tissue disorder presenting with cardiovascular, respiratory, gastrointestinal, and skeletal system findings. Fewer than 100 patients were reported until recently, and all molecularly confirmed cases had de novo heterozygous gain-of-function mutations in the SMAD4 gene. Dysregulation of the TGF-beta signaling pathway leads to axial and appendicular skeleton, connective tissue, cardiovascular system, and central nervous system abnormalities. Case Presentation: Two siblings, 12 and 9 years old, were referred to us because of intellectual disability, neurodevelopmental delay, and dysmorphic facial features. Physical examination revealed hypertelorism, strabismus, small mouth, prognathism, short neck, stiff skin, and brachydactyly. Discussion: With a clinical diagnosis of MS, the SMAD4 gene was analyzed via Sanger sequencing, and a heterozygous c.1486C>T (p.Arg496Cys) pathogenic variation was detected in both of the siblings. The segregation analysis revealed that the mutation was inherited from the father who displayed a milder phenotype. Among the 90 patients in the literature, one family was reported in which two siblings carried the same variation (p.Arg496Cys), inherited from the severely affected mother. We are reporting the second family which has three affected family members, a father and two children. We report this study to remind the clinicians to be aware of the parental transmission of SMAD4 variations and also evaluate the parents of the Myhre cases.
Keywords: Tıp; Dahili Tıp Bilimleri; Tıbbi Genetik; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sağlık Bilimleri; Temel Bilimler; Medicine; Internal Medicine Sciences; Medical Genetics; Life Sciences; Molecular Biology and Genetics; Health Sciences; Natural Sciences; GENETİK VE KALITIM; Yaşam Bilimleri (LIFE); GENETICS & HEREDITY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); Genetik (klinik); Moleküler Biyoloji; Genetik; Genetics (clinical); Molecular Biology; Genetics; SMAD4 gene; Intellectual disability; Myhre syndrome; Fertility; NATURAL-HISTORY; GROWTH; MUTATIONS